PENGARUH BUDAYA ORGANISASI DAN TINGKAT KESEJAHTERAAN TERHADAP PROFESIONALISME YANG BERDAMPAK PADA INTEGRITAS PENDIDIK - Muhammad Fauzi; Mohammad Kholil (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2019)
The research of organization culture and welfare rate has been done. But the research that examine what the organization culture influence to profesionalism and integrity of teacher hardly done. Primare date of this research was got from kuesionare of PMS junior high school teacher kendal.the quesionare was given are 50 and all the way back and can used. statistic method that use to examine each hipothesis is path analysis. This research indicate that not all hypothesis can be accept.in result of this analysis are: 1. The influence of organization culture to profesionalism theacher in the real is not proof. 2. The positive influence between welfare rate to profesionalism teacher is fully proof. 3. Organization culture have positive influence to integrity teacher is proof. 4. Walfare rate have direct positive influence to integrity theacher is not proof. 5. The result of this analysis inform there are positive influence between profesionalism and integrity teacher